2008
DOI: 10.1073/pnas.0805676105
|View full text |Cite
|
Sign up to set email alerts
|

Effective rescue of dystrophin improves cardiac function in dystrophin-deficient mice by a modified morpholino oligomer

Abstract: Antisense oligonucleotide-mediated exon skipping is able to correct out-of-frame mutations in Duchenne muscular dystrophy and restore truncated yet functional dystrophins. However, its application is limited by low potency and inefficiency in systemic delivery, especially failure to restore dystrophin in heart. Here, we conjugate a phosphorodiamidate morpholino oligomer with a designed cellpenetrating peptide (PPMO) targeting a mutated dystrophin exon. Systemic delivery of the novel PPMO restores dystrophin to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
258
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(268 citation statements)
references
References 38 publications
7
258
0
1
Order By: Relevance
“…Specifically, the potential of immune response to the delivery enabling peptides needs to be assessed with long-term administration in animal models and ultimately by clinic trials. 21 More recently, we reported that a non-peptide cationic polymer, Octa-guanidine, also significantly improves morpholino-mediated exon skipping and dystrophin expression in both cardiac and skeletal muscles, resulting in amelioration in pathology of dystrophic mdx mice. 22 However, considerable increase in toxicity is expected when the cationic polymers are delivered systemically, although no clear toxicity is observed at the reported doses for a relatively short time period.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Specifically, the potential of immune response to the delivery enabling peptides needs to be assessed with long-term administration in animal models and ultimately by clinic trials. 21 More recently, we reported that a non-peptide cationic polymer, Octa-guanidine, also significantly improves morpholino-mediated exon skipping and dystrophin expression in both cardiac and skeletal muscles, resulting in amelioration in pathology of dystrophic mdx mice. 22 However, considerable increase in toxicity is expected when the cationic polymers are delivered systemically, although no clear toxicity is observed at the reported doses for a relatively short time period.…”
Section: Discussionmentioning
confidence: 96%
“…21,22 Systemic delivery of a morpholino conjugated with the peptide of (RXRRBR)2XB sequence Dose-dependent restoration of dystrophin expression B Wu et al (R:arginine, X:6-aminohexanoic acid, and B:alanine) is able to restore dystrophin to almost normal levels in the cardiac and skeletal muscles in dystrophic mdx mouse. The treatment also increases muscle strength and prevents cardiac pump failure induced by dobutamine stress in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has prompted the search for improved splice correcting AO chemistries [e.g. neutrally charged peptide nucleic acid (PNA) AOs] [8] and the investigation of novel AO-peptide conjugate chemistries [8,9,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%